The relationship between perfectionism and performance failure at national track and field athletes - Erkan, M.; Cepikkurt, F.; Kale Kizildag, E. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Perfectionism is considered to be personality characteristics that reflect an individual`s obsessive pursuits of exceptionally high standards and overly critical appraisals of performance (Hewitt,Flett,2001). In early researches perfectionism seemed as onedimensional, but later,this psychological construct was developed into multidimensional model of conceptualizations(Frost,et al,1990;Flett,Hewitt,1991).The maladaptive perfectionism is the negative aspect of perfectionism and have a positive correlation with fear of failure, anxiety, burnout etc. Fear of failure and continuous search for success are other features of perfectionism. When perfectionist individuals perceive any kind of failure in their work, they begin to evaluate themselves negatively and this results in harsh selfcriticism( Shafran et al,2002).For perfectionists,performance is not only evaluated in the context of achieving a goal,but also evaluated in the context of striving. The purpose of this study was to determine the relations between perfectionism and fear of failure at national athletes. Methods: Volunteered 33 athletes (22males,11females) from track and field national team, aged between 16 to 36 years [Mage(year)=23.52±5.12] participated in the study. Multidimensional Perfectionism Scale for Athletes-MPS(Dunn et al,2002) and Performance Failure Appraisal Inventory-PFAI(Conroy et al, 2002) were used. MPS consists of 30 items and has 4 subscales. In Turkish version of MPS,factor analysis has supported the Scale`s 3 factor (concern over mistakes, perceived parental pressure, personal standards) and 19 items.PFAI consists of 25 items and has 5 subscales.Pearson Moment Correlation Coefficients was used to determine whether there was a relationship or not between perfectionism and fear of failure. Results:The positive correlations were found between subscales of perfectionism and fear of failure(p< .001).Personal standards subscales have no correlation with fear of experiencing shame and fear of devaluing one`s self estimate. Discussion: Results show that negative perfectionism subscales have positive correlation between fear of failure and this findings supported by some of the previous findings(Flett,Hewitt,2006;Frost et al,1993).According to Atkinson(1964),desire to achieve perfection leads to fear of failure; and these negative thoughts leads to stress. Also, perfectionistic persons who live fear of failure in sport area, may have problems in academic and social area too. Consequently, it can be said that perfectionism have positive and negative aspects, and the negative aspect of perfectionism also associated with negative thoughts and feelings.